Automatic Tea Ceremony Teapot Robotic Arm Design Based on TRIZ Principle - Wang, Huayin; Sun, Wei; Feng, Yingzhi; Lv, Lejing; Li, Qianru (Transactions on Engineering and Technology Research, 2024)
With the accelerated pace of modern society, there is a contradiction between the tedious steps of traditional tea ceremony and the convenient lifestyle. In order to solve this problem, this study applies the TRIZ theory to optimize the design of the fully automatic tea ceremony teapot robot arm. Through the "nine-screen method", the traditional tea-making process was comprehensively analyzed, the key steps were identified, and the cultural significance and technical requirements of each step were discussed in depth. Using the "technical contradiction matrix" and "physical contradiction" analysis, the potential contradictions in the tea-making process were revealed, and the "physical field model" was applied to construct the problem model and explore the possible solutions. The problem model was constructed by applying the "Physical Field Model", and possible solutions were explored. The study proposes a fully automated tea art teapot robotic arm design program that integrates several key technology modules such as heating and temperature control, plane movement, lid operation, and pouring and dispensing of tea. The program ensures the quality of tea soup and the experience of traditional tea ceremonies through the well-designed robotic arm structure and improves the efficiency of tea brewing at the same time. The structural safety of the design scheme is verified by stress analysis of the connecting plate of the robotic arm and the connecting plate of the teapot base. Finally, the feasibility and effectiveness of the proposed scheme are verified through kinematic analysis, prototype testing, and user experience evaluation. This study is of great practical significance for the modernization and transformation of the traditional tea ceremony and also provides a reference for the automation of other traditional crafts. With the continuous progress of technology, we expect more innovative products combining traditional culture and modern technology to appear in the future so that traditional art can be revitalized in modern society.